The Relationship Between Knowledge and Nutritional Intake with the Incidence of Anemia in Students at Nusantara Private High School, Lubuk Pakam in 2026 - Marta Aditya Pratiwi; Erika Damayanti; Winda Rizki; Putri Permatasari (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Developing nations continue to face the disproportionate burden of anemia worldwide. Fatigue and impaired cognitive performance in teenagers, as well as impaired motor and behavioral development in children, are all symptoms of this disorder. There is a substantial risk of iron insufficiency in teenage females since their daily iron needs are about 11 mg. In order to sustain development and compensate for iron losses that occur naturally, including during menstruation, the body's iron needs rise throughout adolescence. Adolescent girls at SMA Swasta Nusantara Lubuk Pakam were the subjects of this research, which sought to examine the correlation between anemia rates and variables such nutritional intake and knowledge. The Spearman Correlation test was used to analyze the data in a cross-sectional research. With a p-value of 0.000 (<0.05), the statistical test findings demonstrated a strong correlation between dietary consumption and knowledge and the occurrence of anemia. With p-values for carbohydrates (1.000), protein (0.716), and fat (0.062) all higher than 0.05, there was no statistically significant correlation between macronutrient consumption and the prevalence of anemia. Because of this, researcher may infer that dietary carbs, proteins, and fats do not contribute to the prevalence of anemia, and we reject the alternative hypothesis (Ha) for this variable.